Danforth's handbook of obstetrics and gynecology - Scott, James R (Lippincott - Raven Publishers, 1996)
Pocket-sized version of the textbook, distills the essentials and makes them available for quick reference. New to this edition, 32 color figures, 16 new chapters, 200 new drawings.
Keywords: gynekologie a porodnictví; porodnictví; gynekologie; Gynecology; Obstetrics